The Effect of Process Parameters on Residual Stress in a Friction Stir Processed Cast Aluminium Alloy AlSi9Mg - WĘGLOWSKI, Marek Stanislaw; SĘDEK, Piotr; HAMILTON, Carter (Engineering Transactions, 2016)
The effect of friction stir processing (FSP) on residual stress in a modified cast aluminium alloy AlSi9Mg is presented. The influence of rotational speed and tool type were analysed. The trepanation method was utilized to experimentally measure the residual stress. The results indicate that an increase in rotational speed causes an increase in residual stress. The region around the FSP bead was characterised by tensile residual stress fields which were balanced by compressive stresses in the parent material. A higher residual stress was observed on the advancing side than on the retreating side. Moreover, this asymmetry in residual stress distribution is due to the asymmetry in the volume of material plasticized along the advancing and retreating sides of the stir zone, generating the observed heat distribution. A higher level of residual stress was achieved with the Triflute tool than with a conventional tool.